Changing the Scenario with Children’s Literature: Promoting Environmental Responsibility through Children's Literature (Journal of Advances and Scholarly Researches in Allied Education, 2021)
It is not enough to simply teach children to read we have to give them something worth reading. Something that will stretch their imaginations—something that will help them make sense of their own lives and encourage them to reach out toward people whose lives are quite different from their own.—Katherine PattersonToday's word is full of discussions, conferences and seminars on topics related to environmental conservation but only words without positive thoughts and actions cannot change the scenario. If we really want to change our coming days, we need to sensitize our children about environment, its beneficial aspects and conservation. This paper is focused on Children's books about the environment. Reading books does not only strengthen our brain but it really changes our mindset. We can implant seed of sustainable development in our future generation by making them a minute observer of nature and its urgent needs. The paper provides a glimpses of various Children's books by Ruth Spiro, Sophia M. Gholz, Lee Constable, Jeanette Winter, William Kam kaamna etc. All these writers all around the World are trying to guide the new energy towards waste-management and eco-experiments.This paper is a discussion on the stories presented in famous Children's books and how the writers are developing a sense of responsibility in kids towards making our Earth a safer planet for many generations.